Mental Health and Covid-19: The Malaysian Students’ Perspective - Anushia Chelvarayan; Amir Arsyad Bin Abdul Razak; Yeo Sook Fern (Research Synergy Foundation, 2023)
This study is a preliminary study of factors affecting the mental health of Malaysian students during the Covid19 pandemic. Mental health can be a major public health issue for students worldwide, with up to 20% of the population suffering from some form of mental illness. Malaysia accounts for about 30% of global suicides, and other mental disorders are much more common than in other countries. Many students said the lockdown made them emotionally distressed. Symptoms of stress, anxiety, loneliness, and depression intensified after the COVID-19 crisis and confirmed that a lack of friendship can lead to depression, anxiety and stress. Therefore, the purpose of this study is to supplement the existing literature by examining the psychological stress experienced by Malaysian university students during the Covid19 lockdown. This study which focuses on economic problem, quarantine, change in sleep pattern, the impact of social media and fear and anxiety for personal and family as independents variables gauges them as the influencing factors for the University students’ mental health in Malaysia. With a total of 200 respondents, the data was analysed through a cross sectional, convenience sampling using SPSS concluded that only change in sleep pattern and the fear and anxiety for personal and family health were significant factors in influencing students’ mental health during Covid-19. This study is expected to help policy makers and practitioners design appropriate and effective